2015
DOI: 10.2989/00306525.2015.1005558
|View full text |Cite
|
Sign up to set email alerts
|

Blue Petrels Halobaena caerulea discovered breeding on Gough Island

Abstract: The Blue Petrel Halobaena caerulea breeds at five subantarctic island groups and at islands off southern Chile in a narrow latitudinal band from 47° to 56° S on either side of the Antarctic Polar Front. We found a colony on Gough Island (40° S, 10° W), central South Atlantic Ocean, more than 700 km north of its known breeding range. Breeding appears to take place later than at colonies farther south. Although the colony is in a fairly frequently visited part of the island, it might have been overlooked rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Campos & Granadeiro (1999) recorded white-faced storm petrels on Selvagem Grande Island leaving their eggs for 1–6 days, resulting in 17/35 (48.6%) eggs failing due to mice predation, 12 of which were eaten by mice within 24 hours of being left alone. Temporary egg desertion is also frequent in blue petrels (Ancel et al 1998), a species recently found breeding on Gough Island in the summer of 2014 (Ryan et al 2015).
Fig.
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Campos & Granadeiro (1999) recorded white-faced storm petrels on Selvagem Grande Island leaving their eggs for 1–6 days, resulting in 17/35 (48.6%) eggs failing due to mice predation, 12 of which were eaten by mice within 24 hours of being left alone. Temporary egg desertion is also frequent in blue petrels (Ancel et al 1998), a species recently found breeding on Gough Island in the summer of 2014 (Ryan et al 2015).
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…A second population of prions was recently discovered breeding in the summer on Gough Island, morphologically similar to MacGillivray’s prion ( Pachyptila macgillivrayi Mathews) from Amsterdam and St Paul islands in the temperate Indian Ocean (Ryan et al 2014). Blue petrels ( Halobaena caerula Gmelin) were also found breeding on Gough Island for the first time in 2014 (Ryan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some birds disperse north off the west coast of South America in winter, but elsewhere they seldom venture north of the Subtropical Front (Brown et al 1986, Ryan et al 1989). Almost the entire population of some 2.4 million pairs breeds from 47 to 56°S at five sub-Antarctic island groups and islands off the southern tip of South America (Dilley et al 2017), with a small population recently discovered farther north on Gough Island (40°S, 10°W; Ryan et al 2015). Adults breed in early summer, returning to colonies from the end of August, laying eggs in late October and fledging chicks in late January–early February (Marchant & Higgins 1990; although breeding occurs ~1 month later at Gough Island; Ryan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Almost the entire population of some 2.4 million pairs breeds from 47 to 56°S at five sub-Antarctic island groups and islands off the southern tip of South America (Dilley et al 2017), with a small population recently discovered farther north on Gough Island (40°S, 10°W; Ryan et al 2015). Adults breed in early summer, returning to colonies from the end of August, laying eggs in late October and fledging chicks in late January–early February (Marchant & Higgins 1990; although breeding occurs ~1 month later at Gough Island; Ryan et al 2015). Moult takes place immediately after breeding, with some birds dropping up to three inner primaries even before leaving their colonies (Marchant & Higgins 1990).…”
Section: Introductionmentioning
confidence: 99%
“…1) suggests that the female northern giant petrel was responsible for plucking the feathers and not a skua. Furthermore, in 2014, while surveying blue petrels ( Halobaena caerulea ) on Gough Island (Ryan et al 2015), two nearby ( c. 1 m distance) incubating southern giant petrels ( Macronectes giganteus ) showed elevated interest, moving their heads towards birds temporarily removed from burrows for examination (C.W. Jones, personal observation), which suggests that giant petrels may capitalize on burrowing petrels as opportunistic prey available at their nests.…”
Section: Discussionmentioning
confidence: 99%